Why can insects not biosynthesize cholesterol?. Issue 3 (13th November 2022) - Haas, Eric; Kim, Yonggyun; Stanley, David
Abstract: Two aspects of insect lipid biochemistry differ from the mammalian background. In one aspect, nearly a hundred years ago scientists demonstrated that the polyunsaturated fatty acid (PUFAs), linoleic acid (LA; 18:2n‐6) is an essential nutrient in the diets of all mammals that have been studied in that regard. An unknown number of insect species are able to biosynthesize LA de novo. Some species take the biosynthesized LA into fatty acid elongation/desaturation pathways to produce other PUFAs, 18:3n‐6, 20:3n‐6 and 20:4n‐6. A couple of species use the de novo produced LA to biosynthesize prostaglandins and other eicosanoids, short‐lived signal moieties that mediate important physiological actions in immunity and reproduction. Insects differ from mammals, also, in their lack of genes that encode enzymes acting in biosynthesis of cholesterol. Insects require dietary cholesterol to meet their cellular, physiological, developmental, and reproductive needs. Looking at a broader view of invertebrate biochemistry, most protostomes lost all or most genes involved in cholesterol biosynthesis. The massive gene loss occurred during the Ediacaran Period, which lasted 96 million years, from the end of the Cryogenian Period (635 million years ago; MYA) to the beginning of the Cambrian Period (538.6 MYA). The key point here is that the inability to biosynthesize cholesterol is not limited to insects; it occured in most protostomes. We address the protostome need and benefits of acquiring exogenous sterols. Abstract : Diversification of cholesterol biosynthesis among metazoans. Highlight: 1. Lack of genes that encode enzymes acting in biosynthesis of cholesterol in insects 2. Moreover, most protostomes lost all or most genes involved in cholesterol biosynthesis. 3. The massive gene loss occurred during the Ediacaran Period.